Menstrual cycles and the impact upon performance in elite British track and field athletes: a longitudinal study - Jones, Benjamin P.; L'Heveder, Ariadne; Bishop, Charlotte; Kasaven, Lorraine; Saso, Srdjan; Davies, Sarah; Chakraverty, Robin; Brown, James; Pollock, Noel (Frontiers in Sports and Active Living, 2024)
Objective: To assess the prevalence of menstrual disorders and the perceived effect of menstrual cycles upon performance in elite athletes.Methodology: A longitudinal survey in the form of a questionnaire was sent to female track and field athletes at British Athletics every 6 months, over a five-year period between 1 st October 2014 and 1 st October 2019 in the United Kingdom (UK).Results: 128 athletes completed an average of 4.2 ± 2.9 questionnaires across the study period. The mean age of menarche was 14.2 ± 1.4 years, 13.4 ± 1.3 years and 12.8 ±1.4 years in endurance, power, and thrower athletes respectively (p<0.05). Two-thirds (66%; n=82) reported consistently regular cycles, 30% (n=37) irregular at some point during the period of observation and 4% (n=5) were amenorrhoeic. 87 athletes (68%) reported dysmenorrhoea and 40 (31%) menorrhagia. More than three quarters (76.8%; n=96) described their cycle negatively affected performance. Amongst those who reported when the negative impact occurred (n=91), 40% (n=36) reported this in the late luteal phase and 35% (n=32) during the early follicular phase. 79% (n=100) of athletes reported at least one cyclical symptom, of which bloating, lower back and pelvic pain were most frequently experienced.This data highlights the complex interrelationship between women's health and elite athletic performance. Athletes perceive a negative impact from their menstrual cycles upon performance with a desire to manage these more effectively, particularly during competition. Female reproductive health expertise in the multi-disciplinary management of elite athletes is required.